On Otxuruu, a new genus of Theridiosomatidae Simon, 1881 (Araneae: Araneoidea) from the Neotropical region - Pantoja, Paulo; Bonaldo, Alexandre B.; Brescovit, Antonio D.; Labarque, Facundo M. (Zootaxa, 2025)
A new Theridiosomatidae genus of the subfamily Epeirotypinae is described to allocate a new species from the Brazilian and Ecuadorian Amazon, Otxuruu fallax gen. & sp. nov. The new genus/species can be distinguished from other Theridiosomatidae genera/species by the presence of multiple dorsolateral tubercles on the opisthosoma; the male palp bearing two embolic apophyses, a long, slender and coiled prolateral apophysis, and a flat, large, and subquadrate (in mesal view) retrolateral one; and female epigyne with a wider than long scape; spermathecae cylindrical, longer than wide; and distal sector of the copulatory duct robust and flat.